(untitled) - Gibbons, Alan (Cambridge, 1989)
This largely self-contained text is an introduction to the field of efficient parallel algorithms and to the techniques for efficient parallelism, that presumes no special knowledge of parallel computers or particular mathematics. The book emphasizes designing algorithms within the timeless and abstracted context of a high-level programming language rather than within highly specific computer architectures. This is an approach that concentrates on the essence of algorithmic theory, determining and taking advantage of the inherently parallel nature of certain types of problems. The authors present regularly-used techniques and a range of algorithms including some of the more celebrated ones. Nonspecialists considering entering the field of parallel algorithms, as well as advanced undergraduate or postgraduate students of computer science and mathematics will find this book helpful.
Keywords: Parallel programming (Computer science),Lập trình song song (khoa học máy tính)